Toward the Vision of a Literate Society. Background Paper Prepared for Project on Adult Literacy - Delker, Paul V.; Yakowicz, William J.; Southport Inst. for Policy Analysis, Inc., CT. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Estimates of the true extent of illiteracy among the United States's adult population vary widely. The Department of Education has estimated that there are 23 million illiterate Americans and an additional 46 million American who function only marginally in an increasingly technological society. Federal support for adult literacy began in 1965 when funds for adult basic education (ABE) began filtering to state education departments under the Economic Opportunity Act of 1964. During ABE's first decade there was some success in establishing broadly available programs giving adults greater access to literacy and basic education assistance. Nevertheless, as of 1975, literacy programs were only reaching a small fraction of those who needed them. Since 1975, significant developments have occurred and funding has increased substantially. Beginning in 1983, the literacy initiative, while not providing any additional fiscal support, attempted to extend literacy services through awareness campaigns, the use of volunteer tutors, and privately funded support. Although substantial progress has been made, many problems remain. Adult literacy has often been supported as a means of achieving other economic and social development policies. Although this is both appropriate and commendable, policymakers must not lose sight of adult literacy and learning as ends in themselves. (MN)
Availability: The Project on Adult Literacy, Suite 415, 440 First Street, N.W., Washington, DC 20001.
ERIC Note: For related documents, see CE 051 679-686.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Literacy; Educational Change; Educational Needs; Educational Objectives; Educational Policy; Federal Legislation; Literacy Education; Program Development; Information Analyses; Opinion Papers